A step forward understanding HIV-1 diversity. Issue 1 (December 2016) - Smyth, Redmond; Negroni, Matteo
Abstract Human immunodeficiency virus (HIV) populations are characterized by extensive genetic diversity. Antigenic diversification is essential for escape from immune selection and therapy, and remains one of the major obstacles for the development of an efficient vaccine strategy. Even if intensive efforts have been made for understanding the molecular mechanisms responsible for genetic diversity in HIV, conclusive data in vivo is still lacking. Recent works have addressed this issue, focusing on the identification of the sources of genetic diversity during in vivo infections and on the estimate of the pervasiveness of genetic recombination during replication in vivo. Surprisingly, it appears that despite the error-prone nature of the viral polymerase, the bulk of mutations found in patients are indeed due to the effect of a cellular restriction factor. This factor tends to hypermutate the viral genome abolishing viral infectivity. When hypermutation is incomplete, the virus retains infectivity and converts the effect of the cellular factor to its advantage by exploiting it to generate genetic diversity that is beneficial for viral propagation. This view contrasts the long-standing dogma that viral diversity is due to the intrinsic error-prone nature of the viral replication cycle. Besides hypermutations and mutations, recombination is also a pervasive source of genetic diversity. The estimate of the frequency at which this process takes place in vivo has remained elusive, despite extensive efforts in this sense. Now, using single genome amplification, and starting from publically available datasets, it has been obtained a confirmation of the estimates previously made using tissue culture studies. These recent findings are presented here and their implications for the development of future researches are discussed.